1990
DOI: 10.1136/adc.65.2.234
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus epidermidis and retention of neonatal percutaneous central venous catheters.

Abstract: The percutaneous insertion of central venous catheters has become an established practice on many neonatal units. We describe four low birthweight babies, whose catheters became tethered in the vein, and discuss the management of this unusual complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 5 publications
(1 reference statement)
1
16
0
Order By: Relevance
“…But vessels used for midline catheters have a narrower diameter and slower blood flow than central veins. Administration of hyperosmotic solution into these vessels can cause local complications such as vasculitis and fibrin sheath or thrombus formation, and infrequently result in removal difficulties 17 . In the present study the removal difficulty was rare, being similar in incidence to pleural effusion/ascites.…”
Section: Discussionsupporting
confidence: 43%
“…But vessels used for midline catheters have a narrower diameter and slower blood flow than central veins. Administration of hyperosmotic solution into these vessels can cause local complications such as vasculitis and fibrin sheath or thrombus formation, and infrequently result in removal difficulties 17 . In the present study the removal difficulty was rare, being similar in incidence to pleural effusion/ascites.…”
Section: Discussionsupporting
confidence: 43%
“…A recent King's Fund conference concluded that reuse of items manufactured for single patient use was undesirable and recommended development of guidelines governing reuse at district levels. 3 This survey aimed to determine current cleaning and reuse practices and to obtain information on the advice and support given to parents issued with a home nebuliser in a nationally representative sample of paediatric wards in England. We also sought to establish whether guidelines governing reuse were available at district health authority level.…”
Section: Introductionmentioning
confidence: 99%
“…6 Retained catheters are a rare complication that has been reported to be associated with infection with both M. furfur and S. epidermidis. 3,4 The most likely mechanism for catheters adherence is the development of thrombi or fibrin sheaths on the surface of infected catheters, causing the catheter to become adherent to the vein wall. 3,9,16 In our experience, adhered catheters can often be removed with continuous, gentle traction, using the technique described by Gladman et al 4 However, catheter breakage can occur, resulting in the need for surgical removal of catheter fragments, 3 or retrieval during cardiac catheterization.…”
Section: Discussionmentioning
confidence: 99%